Population genetic implications from sequence variation in four Y chromosome genes - Peidong Shen; Frank Wang; Peter A. Underhill; Claudia Franco; Wei-Hsien Yang; Adriane Roxas; Raphael Sung; Alice Lin; Richard W. Hyman; Douglas Vollrath; Ronald W. Davis; L. Luca Cavalli-Sforza; et al. (2000)
Some insight into human evolution has been gained from the sequencing of four Y chromosome genes. Primary genomic sequencing determined gene SMCY to be composed of 27 exons that comprise 4,620 bp of coding sequence. The unfinished sequencing of the 5′ portion of gene UTY1 was completed by primer walking, and a total of 20 exons were found. By using denaturing HPLC, these two genes, as well as DBY and DFFRY , were screened for polymorphic sites in 53–72 representatives of the five continents. A total of 98 variants were found, yielding nucleotide diversity estimates of 2.45 × 10 −5 , 5.07 × 10 −5 , and 8.54 × 10 −5 for the coding regions of SMCY , DFFRY , and UTY1 , respectively, with no variant having been observed in DBY . In agreement with most autosomal genes, diversity estimates for the noncoding regions were about 2- to 3-fold higher and ranged from 9.16 × 10 −5 to 14.2 × 10 −5 for the four genes. Analysis of the frequencies of derived alleles for all four genes showed that they more closely fit the expectation of a Luria–Delbrück distribution than a distribution expected under a constant population size model, providing evidence for exponential population growth. Pairwise nucleotide mismatch distributions date the occurrence of population expansion to ≈28,000 years ago. This estimate is in accord with the spread of Aurignacian technology and the disappearance of the Neanderthals.